Sharia Credit Card in The View of Maqasid al-Sharia - Rusdiana Priatna Wijaya; Nurizal Ismail (AL- IKTISAB Journal of Islamic Economic Law, 2020)
Islam is the perfect religious concept, all of life's activities are measured in the purpose of sharia enforcement. Maqashid sharia is a benchmark in determining activity in the determination, whether it is by these objectives or not. Credit card is a form of facility created to facilitate consumers in making transactions. This product is multiplying and changing the paradigm of consumers in making transactions in the digital era. Credit card has many benefits and functions, one of its functions is substituted for cash. Method of this study using literacy, data collection and collection of objects. The finding is that the contemporary scholars agree that in practice sharia credit cards are permissible as long as there are no aspects of gharar, usury, but also contain the maslahah of the users. DSN MUI responded favourably to the credit card with the issuance of the fatwa DSN No. 54/DSN/-MUI/X/2006 concerning KKS (Sharia Credit Card).